Investigating host and pathogen biomarkers of mycobacterium bovis and nontuberculous mycobacterial infection in African buffaloes (Syncerus caffer) - Clarke, Charlene (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.